Role of Vitamin D For Oral Health and Overall Health - K.Sheela1 , Dhanasekhar Kesavelu1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Vitamin D, sometimes called the “sunshine vitamin” is produced in our skin in response to sunlight.It’s a fat-soluble vitamin in a family of compounds that includes vitamins D-1, D-2, and D-3.Our bodyproduces vitamin D naturally when it’s directly exposed to sunlight. Vitamin D has several importantfunctions. Perhaps the most vital are regulating the absorption of calcium and phosphorus, and facilitatingnormal immune system function. Getting a sufficient amount of vitamin D is important for normal growthand development of bones and teeth, as well as improved resistance against certain diseases. Nowadays,Vitamin D deficiency patients are identified in various medical fields and it is necessary to understand thesymptoms, pathophysiology and therapeutic measures to overcome the deficiency of this vitamin in variousage groups from pediatric to geriatric.